Magnetic Surgery: Results From First Prospective Clinical Trial in 50 Patients. Issue 1 (January 2018) - Rivas, Homero; Robles, Ignacio; Riquelme, Francisco; Vivanco, Marcelo; Jiménez, Julio; Marinkovic, Boris; Uribe, Mario
Abstract : Objective: To evaluate a new magnetic surgical system during reduced-port laparoscopic cholecystectomy in a prospective, multicenter clinical trial. Background: Laparoscopic instrumentation coupled by magnetic fields may enhance surgeon performance by allowing for shaft-less retraction and mobilization. The movements can be performed under direct visualization, generating different angles of traction and reducing the number of trocars to perform the procedure. This may reduce well-known associated complications of trocars, including incisional pain, scarring, infection, bowel, and vascular injuries, among others. Methods: A prospective, multicenter, single-arm, open-label study was performed to assess the safety and performance of a magnetic surgical system (Levita Magnetics' Surgical System). The investigational device was used during a 3-port laparoscopic technique. The primary endpoints evaluated were safety and feasibility of the device to adequately mobilize the gallbladder to achieve effective exposure of the targeted surgical site. Patients were followed for 30 days postprocedure. Results: Between January 2014 and March 2015, 50 patients presenting with benign gallbladder disease were recruited. Forty-five women and 5 men with an average age of 39 years (18–59), average body mass index of 27 kg/m 2 (20.4–34.1) and an average abdominal wall thickness of 2.6 cm (1.8–4.6). The procedures were successfully performed in all 50 patients. No device-related serious adverse events were reported. Surgeons rated as "excellent" (90%) or "sufficient" (10%) the exposure of the surgical site. Conclusions: This clinical trial shows that this new magnetic surgical system is safe and effective in reduced-port laparoscopic cholecystectomy. Abstract : Supplemental Digital Content is available in the text